P149 Identification of late asthmatic reactions using the 95% confidence interval method of stenton. (December 2018) - Moore, VC; Walters, GI; Roberston, AS; Burge, PS
Abstract : Background: Specific Inhalation challenge (SIC) is the reference standard for the diagnosis of occupational asthma. A positive non-specific challenge has been defined as a FEV1 fall varying from 10% (exercise) to 20% (methacholine); international guidelines (without specific evidence) recommend a 15% fall compared with a control exposure as a significant reaction for an occupational SIC. We have used the pooled standard deviation method of Stenton 1 to provide a scientifically valid estimate of the required fall in FEV1 following occupational SIC, and to see if this is related to baseline FEV1 . Methods: 46 workers who underwent inpatient occupational SIC undertook hourly FEV1 measurements for the 3 days before active SIC. 39 workers achieved enough data. For each worker, the pooled standard deviation of all measurements on control days was calculated after excluding the first hour from waking. A positive late reaction was defined as one with 2 consecutive measurements below the 95% CI for unexposed/control days. Results: The mean 95% CI for control day FEV1 was 399 ml (SD 130), or 14.5% (SD 6.4%) of the baseline value. Four workers had late asthmatic reactions identified only by the pooled SD method (% fall in FEV1 11.2%, 11.9%, 12.8% and 8.9%), although one also had an immediate reaction >15%. The 95% CI was increased when there were missing values in the 3 non-exposed/control days. The baseline FEV1 value was not significantly correlated to the absolute 95% CI level in mls required (Pearsons correlation, p=0.630) (figure 1). The 7/46 who did not achieve enough data were due to too few readings (5), being too unstable (1) or performing technically unacceptable measurements (1). Conclusions: The aim of SIC is to identify the specific cause of asthma with sufficient certainty that any reaction is due to the specific exposure rather than measurement inaccuracy, spontaneous diurnal changes or other factors, while inducing the least possible deterioration in the workers asthma. The pooled standard deviation method for defining late asthmatic reactions has scientific validity, accounts for inter-patient spirometric variability and can identify clinically relevant late asthmatic reactions from smaller exposures. Reference: ERJ 1994;7:806.